5x – 2 (2x – 7) = 2 (3x – 1) + 7/2​

Question

5x – 2 (2x – 7) = 2 (3x – 1) +
7/2​

in progress 0
Lyla 3 weeks 2021-10-05T05:07:46+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-05T05:08:46+00:00

    Answer:

    5/2 is ur answer

    Step-by-step explanation:

    pls mark as brainliest , rate , thank and follow me

    0
    2021-10-05T05:09:22+00:00

    Step-by-step explanation:

    by multiplying the brackets and opening them

    5x-4x+14=6x-2+3.5

    x+14=6x+1.5

    5x=12.5

    x=25/10 or 5/2  

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )